The Practice of Yoga and Ayurveda in the Management of Anxiety, Hypertension and Diabetes Mellitus. - Monica , K P; Nagarajan, Kavya; Bhat, Sulochana (International Research Journal of Ayurveda & Yoga, 2023)
Ayurveda is a comprehensive system that concentrates on repeated consciousness. Hypertension, also known as high or raised blood pressure, is a condition in which the blood vessels have persistently raised pressure. It stands to be the most focused disease due to its high mortality rate. Diabetes is a metabolic disorder that stands second to hypertension as a great concern repeated yoga practice and following Ayurveda together show wonderful results in treating various diseases. And this technique can help with long-term stress or stress related to various health problems such as heart disease. Relaxation techniques are a great way to help with stress management. It’s the process that decreases the stress effects on your mind and body. Yoga, a form of physical activity, is rapidly gaining in popularity and has many health benefits. In this study, the effect of yoga therapy, and how it worked in controlling hypertension immediately after the Deep Relaxation Technique (DRT) and Ayurveda medicines on Hypertension (HTN) and Diabetes Mellitus (DM) have been discussed.